Desarrollo de experiencias mediante una familia de objetos, que ayuden al fortalecimiento de las competencias de la inteligencia emocional en los niños de 2 a 5 años. - Merchán Merchán, María Fernanda (Universidad Antonio Nariño, 2023)
This document is made in order to obtain the professional title of Industrial Design of the Antonio Nariño University, has the objective of being completed for the first period of the year 2022, to be presented to the juries at the end of June.